The rule of faith : Scripture, canon, and creed in a critical age - Radner, Ephraim, 1956-; Sumner, George R., 1955- (HarrisBurg, Pennsylvania : Morehouse Publishing, 1998)
Rev. lectures presented at a conference held in Jan. 1997 in Charleston, S.C., sponsored by Scholarly Engagement with Angllican Doctrine.
Includes bibliographical references.
Keywords: Jesus Christ -- Person and offices -- Doctrines -- Congresses; Episcopal Church -- Doctrines -- Congresses; Jesus Christ -- Person and offices -- Biblical teaching -- Congresses; Bible -- Evidences, authority, etc. -- Congresses